Motivational implications of the word-count tracking strategy for improving writing fluency: A study of Saudi undergraduate EFL learners - Shahzad-ul-Hassan Farooqi (Journal of Pedagogical Research)
This study aims at determining the efficacy and motivational implications of word count tracking as a viable technique for improving writing output among Saudi EFL undergraduates. An intensive Writing Program was conducted at English Department Al-Majmaah University with two groups who were taught through two different approaches. The experimental group (n=23) took a writing session once a week (for six weeks) with word-count tracking strategy besides their regular credit hours writing classes, while the control group (n=22) was taught through conventional approach. The main hypothesis was that the experimental group will have higher mean score than the control group after the implementation of word-count tracking strategy. The difference between the mean score of pre-test and post-test of the experimental group and the control group was found statistically significant at p<.05. The experimental group, despite achieving lower mean score in the pre-test, made 48.51% improvement in the post-test, while the control group showed only 20.33 % output increase. Hence, the study deduced that the word-count tracking technique improved the writing fluency and motivation of students and should be implemented by the writing teachers. The researcher also administered a questionnaire at the end of the study to evaluate perception of the students toward this technique, the writing program and their overall motivational level after this program which showed that students had positive perception towards word-count and believed that it had enhanced their motivation as well as writing fluency.